TWO GENIUS – TWO PRECIOUS - Saydazimov Asroriddin Tokhirjon ugli (Galaxy International Interdisciplinary Research Journal, 2022)
Zahiriddin Muhammad Babur was an important figure in Middle Eastern culture, literature, and poetry. He was a writer, poet, scholar, statesman, and commander. Zahiriddin Muhammad Babur was born in Andijan on February 14, 1483, into the family of Umar Sheikh Mirzo, the Fergana nation's king. The struggle for control in Central Asia and Khorasan between several governors, brothers, nieces and nephews, and the enormous power created by their great-grandfather Amir Temur ultimately increased during this period. Nizamiddin Mir Alisher Navoi, a major figure in 15th-century world spirituality, was born on the 17th day of Ramadan (February 9, 1441) in Herat, Afghanistan. Herat was the second capital of Amir Temur's immense kingdom in the first half of the 15th century, and one of the most prosperous towns under Shahrukh Mirza, Temur's youngest son. Alisher's family was related to the Timurid emperor and held some power in the kingdom. Giyosiddin Muhammad, the future poet's father, gave considerable care to his son's upbringing. In this article we can discuss these two precious and genius people and then we try to give our own opinions as well.